Les Ateliers d’Antoine : apports de la Théorie des Opérations Énonciatives en didactique du français à l’école élémentaire - Lionel AUDION (Corela)
After showing the necessity to reconfigure the didactics of mother tongue grammar at the French elementary school level, this article describes the scheme I am suggesting to adopt in courses for teachers of elementary school. “Antoine’s Workshops” have been devised for pupils in fourth and fifth grade — 8 to 10 years of age — in order to help them develop a metalinguistic reflection about language problems. This is carried out with a special tool called the “problem-square” and a special ritual : the “acceptability debate”. The novelty of such an approach rests upon a change in the conceptual framework : I suggest that the “Theory of Enunciative Operations” by Antoine Culioli suits children’s needs particularly well and despite its complexity I propose using it at elementary school level to provide teachers with reliable metalinguistic notions.